Fever prevalence and management among three rural communities in the North West Zone, Somalia. - Youssef, R; Alegana, V; Amran, J; Noor, A; Snow, R (2010)
Between March and August 2008 we undertook 2 cross-sectional surveys among 1375 residents of 3 randomly selected villages in the district of Gebiley in the North-West Zone, Somalia. We investigated for the presence of malaria infection and the period prevalence of self-reported fever 14 days prior to both surveys. All blood samples examined were negative for both species of Plasmodium. The period prevalence of 14-day fevers was 4.8% in March and 0.6% in August; the majority of fevers (84.4%) were associated with other symptoms including cough, running nose and sore throat; 48/64 cases had resolved by the day of interview (mean duration 5.4 days). Only 18 (37.5%) fever cases were managed at a formal health care facility: 7 within 24 hours and 10 within 24-72 hours of onset. None of the fevers were investigated for malaria; they were treated with antibiotics, antipyretics and vitamins.